The CD40 agonist HERA-CD40L results in enhanced activation of antigen presenting cells, promoting an anti-tumor effect alone and in combination with radiotherapy - Frankish, Jamie; Mukherjee, Debayan; Romano, Erminia; Billian-Frey, Katharina; Schröder, Matthias; Heinonen, Karl; Merz, Christian; Redondo Müller, Mauricio; Gieffers, Christian; Hill, Oliver; Thiemann, Meinolf; Honeychurch, Jamie; et al. (Frontiers in Immunology, 2023)
Introduction The ability to modulate and enhance the anti-tumor immune responses is critical in developing novel therapies in cancer. The Tumor Necrosis Factor (TNF) Receptor Super Family (TNFRSF) are potentially excellent targets for modulation which result in specific anti-tumor immune responses. CD40 is a member of the TNFRSF and several clinical therapies are under development. CD40 signaling plays a pivotal role in regulating the immune system from B cell responses to myeloid cell driven activation of T cells. The CD40 signaling axis is well characterized and here we compare next generation HERA-Ligands to conventional monoclonal antibody based immune modulation for the treatment of cancer. Methods & results HERA-CD40L is a novel molecule that targets CD40 mediated signal transduction and demonstrates a clear mode of action in generating an activated receptor complex via recruitment of TRAFs, cIAP1, and HOIP, leading to TRAF2 phosphorylation and ultimately resulting in the enhanced activation of key inflammatory/survival pathway and transcription factors such asNFkB, AKT, p38, ERK1/2, JNK, and STAT1 in dendritic cells. Furthermore, HERA-CD40L demonstrated a strong modulation of the tumor microenvironment (TME) via the increase in intratumoral CD8+ T cells and the functional switch from pro-tumor macrophages (TAMs) to anti-tumor macrophages that together results in a significant reduction of tumor growth in a CT26 mouse model. Furthermore, radiotherapy which may have an immunosuppressive modulation of the TME, was shown to have an immunostimulatory effect in combination with HERA-CD40L. Radiotherapy in combination with HERA-CD40L treatment resulted in an increase in detected intratumoral CD4+/8+ T cells compared to RT alone and, additionally, the repolarization of TAMs was also observed, resulting in an inhibition of tumor growth in a TRAMP-C1 mouse model. Discussion Taken together, HERA-CD40L resulted in activating signal transduction mechanisms in dendritic cells, resulting in an increase in intratumoral T cells and manipulation of the TME to be pro-inflammatory, repolarizing M2 macrophages to M1, enhancing tumor control.